Pengaruh Pengetahuan Perpajakan, Kondisi Keuangan dan Lingkungan terhadap Kepatuhan Wajib Pajak UMKM: (Studi Kasus UMKM di Kota Bandar Lampung) - Agung Riskillah; Irawan Irawan; Artie Arditha Rachman (Jurnal Ilmiah ESAI, 2022)
The purpose of this study was to determine the effects of taxation knowledge, financial condition, and environment on UMKM taxpayers’ compliance. The research method used was quantitative method. The population in this study were UMKM practitioners in Bandar Lampung City with a total sample of 100 respondents. The data collection technique used was a questionnaire using a Likert instrument measuring scale. The data analysis technique used was Multiple Linear Regression. The results of the study partially shows that there is a positive influence of taxation knowledge and environment variables on UMKM taxpayers’ compliance in Bandar Lampung City, while the financial condition variable does not affect UMKM taxpayers’ compliance in Bandar Lampung City, while simultaneously taxation knowledge, financial conditions, and the environment have positive effects on UMKM taxpayers’ compliance in Bandar Lampung City.